Transformation of Knowledge and Skills in Building Traditional Bugis Homes in Sidrap District - Jalil; Bundu Patta; Sinring Abdullah (PT FORMOSA CENDEKIA GLOBAL, 2023)
This research is a qualitative descriptive research and aims to find out knowledge, skills, values and how the pattern of knowledge transformation in the manufacture of traditional Bugis houses. The results of the study found, the knowledge that needs to be possessed is that the additional elements in the traditional Bugis house model affect the price of the house, the selection of wood as the basic material for the house, the wood that is already in the form of aliri, pattolo, bare', boards, and beams, the basic frame of the house uses class wood one like ironwood, kumea, cat's eye. Meanwhile, for secondary purposes, use second-class wood such as kalapi, cenrana and lime wood. Basic knowledge of carpentry must understand the determination of the basic elements of the house, the structure of the house, the location and codes for the components of the house, how to install the roof, floors, walls and stairs. Basic carpentry skills must be able to use a variety of traditional and modern carpentry tools. The values contained in the manufacture of traditional Bugis houses are discipline, firmness, responsibility, mutual respect, mutual cooperation, cultural preservation, optimism, thoroughness, accuracy, serenity, and motivation. Form of transformation in the manufacture of traditional Bugis houses because it lasts for a long time